A Factorial Validation of Parental Mediation Strategies with Regard to Internet Use. Issue 2 (26th June 2017) - Symons, Katrien; Ponnet, Koen; Emmery, Kathleen; Walrave, Michel; Heirman, Wannes
This study investigated the strategies which parents employ in order to mediate their adolescent child's internet use, thereby including the perspectives from the mother, the father and an adolescent child aged 13 to 18. Data from 357 families ( n = 1071) were analyzed. Parental mediation strategies were inductively derived from a wide range of concrete mediation practices. Factor analysis yielded the same six factor solution for each informant, resulting in the identification of six distinct parental mediation strategies. Differences occurred between the three informants in terms of the quantity of mediation taking place. Parental mediation was predicted by the child's age, but less by the parents' age and the child's gender.